New Frontiers in Social Innovation Research - Nicholls, Alex; Simon, Julie; Gabriel, Madeleine (Springer Nature, 2015)
Social Policy, Politics and Economics of Welfare, Business and Management, Innovation, Sociology, Economic Sociology, Politics, Citizenship, Social Policy and Welfare